Correlation between serum laminin levels and prognosis of acute myocardial infarction - Xu, Lou-Yuan; Xie, Ling; Wang, Jing; Chen, Hai-Xiao; Cai, Hong-Li; Tian, Li-Jun; Zhang, Qing (Frontiers in Cardiovascular Medicine, 2022)
Background: Acute myocardial infarction (AMI) is a critical disease in cardiovascular disease，Laminin (LN) is involved in the process of myocardial fibrosis and ventricular remodeling, but there is no study on the correlation between LN and the prognosis of AMI. Purpose: To explore the predictive value of LN level on major adverse cardiovascular events (MACE) in patients with AMI within 6 months. Methods: 202 patients with acute myocardial infarction who were hospitalized in the Department of Cardiology of the Second Affiliated Hospital of Nantong University from December 2019 to December 2020 were included. The observation end point was the occurrence of MACE. The predictors of MACE were screened by single factor analysis and multi factor analysis, Finally, the receiver operator characteristic curve (ROC curve) was used to analyze the predictive value of LN for MACE in patients with AMI. Results: A total of 47 patients developed MACE. Univariate analysis showed that smoking, emergency percutaneous coronary intervention (EPCI), age, cardiac troponin I (c-TNI), N-terminal B-type natriuretic peptide precursor (NT-proBNP) level and LN level were associated with the occurrence of MACE (p<0.05). Multivariate analysis showed that LN was an independent predictor of MACE (OR=1.021, 95%CI: 1.014-1.032, p<0.001). According to the ROC curve, LN can be used as an effective factor to predict the occurrence of MACE (AUC=0.856, 95%CI: 0.794-0.918, p<0.001). According to the cut-off value, LN>79.96 mmol/L indicates a poor prognosis of AMI. Conclusions: LN is a predictor of MACE in AMI. Provide new ideas for the prevention and treatment of AMI.